(untitled) (Fiep Bulletin - online, 2014)
As part of the Extension Community Projects of the Dom Bosco Catholic University (UCDB), The Laboratory for Physical Aptitude Evaluation (LPAE), develops diagnosis of physical aptitude and guidance on practice of physical exercises so as to promote community health. The Viação Campo Grande Public Transport Company aims to improve its employee’s life quality as well as preserve the environment. In one of these actions, it developed a partnership with UCDB in order to give a profile of the workers’ physical aptitude. This work aims to identify obesity cases and health risk factors among the staff of the Viação Campo Grande public transport company. The methodology consists of collecting anthropometric data. The variables this study were: stature, total corporal weight, abdominal and hip circumference and skin fold. After that we identified the risk factors considered in cases of Obesity, Corporal Mass Rate (CMR) and Waist-Hip Rate (WHR). Analyzing CMR we found among the Administrative staff (n=24), risk factor in 49.83% of the sample and in the Operational staff (n=147) this risk factor rose to 65.97% of the sample. Analyzing Obesity and Waist-Hip Rate, the risk factor was found in 70% of the sample for both Administrative and Operational groups. It is possible to state that the employees of the Viação Campo Grande present high level of risk factors based on the body fat percentage, CMR and WHR.